Geological-geomorphological and geochemical control on low arsenic concentration in the Lerma valley groundwater between the two high arsenic geologic provinces of Chaco-Pampean plain and Puna - Murray, Jesica María (2019)
Argentina is known for having one of the most extensive areas with high arsenic (As) concentration in groundwater in the world. These areas correspond to two main geological provinces, the Puna plateau and the Chaco-Pampean plain. In this large territory, there are some specific environments where the As concentration in groundwater is lower, and in some cases within the recommended limits for drinking water. In our study, we analyze and interpret the low arsenic concentrations reported for the Lerma valley, the easternmost intermontane basin of the Cordillera Oriental, located between the aforementioned high-arsenic geological provinces. The groundwater from this valley is used for the consumption of more than 600.000 inhabitants in the city of Salta and nearby towns. The incipient development of the valley since the late Miocene and the subsequent tectonic and climatic evolution favored low As concentrations with respect to the Puna and the Chaco-Pampean plain. The high-energy sedimentary environments thatcharacterized the area during Plio-Quaternary times and the composition of the sediments have controlled the characteristics of sediments the multilayered aquifer. Moreover, the absence of geogenic arsenic sources, climate, high rain infiltration rate, near neutralpH,redox conditions, and wells construction with screens settledincoarse productive layers favor groundwater of good quality.The geological and tectonic evolution of the Lerma valley could be extrapolated to other similar valleys in the NW of Argentinaand can be useful as tool for exploration of good quality groundwater. This is of high importance in Latin American territories with high As concentration in groundwater such as Argentina.